Badania kliniczne i doświadczalne w chorobach serca, płuc i naczyńIntroducing an experimental heterotopic heart transplantation modelin rat in the Cardiovascular Research Laboratory of the Silesian Centre for Heart Diseases in Zabrze - Śliwka, Joanna; Dołoszyńska, Anna; Sokal, Adam; Kocher, Alfred; Tyrpień, Mirosław; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: Heart transplantation is a well established and accepted treatment of end-stage heart failure and uncorrectable congenital heart disease. Cardiac allograft rejection has been extensively studied and is associated with decreased left ventricular function. The experimental animal model of cardiac transplantation allows tracking and observation of the progress of allograft rejection. Introduction of new pharmacological agents to inhibit either a severe or chronic rejection process presents a formidable challenge and research opportunity. Material and Methods: Experimental allogenic heterotopic heart transplantation was performed in a rat model. Animals were anaesthetized with pentobarbital sodium (0.45 mg per 100 g of body weight). Thirty minutes before the procedure the donor was heparinized with 5000 UI of heparin injected directly into the inferior vena cava (IVC). The donor’s heart was arrested by direct injection of 30 ml of ice-cold high-potassium cardioplegia (Plegisol, Abbott Laboratories). The donor’s heart was then placed in the abdominal cavity of the recipient. After sufficient exposure of the recipient abdominal aorta and IVC, subsequent anastomoses were made using continuous suture: end-to-side donor ascending aorta to recipient abdominal aorta (just below renal arteries), and end-to-side donor pulmonary artery to the recipient’s IVC. Total ischaemia time did not exceed 40 minutes. Animals were then allowed to recover. No immunosuppressive medications were used throughout the entire follow-up. Function of the transplanted heart was assessed weekly by transthoracic echocardiography. Mean time of the follow-up was 20 weeks (±10). Vasculopathy, atrophy of the muscle, and lymphocytic infiltration were subsequently assessed and evaluated. Conclusions: Introducing an experimental animal model of heterotopic heart transplant is a big challenge because of the technical aspects to achieve a stable, repeatable model obtaining anatomic and haemodynamic conditions of the heart.